Kurdistan on the global stage : kinship, land, and community in Iraq - King, Diane E., 1966- (Rutgers University Press, 2014)
Diane E. King has written about everyday life in the Kurdistan Region of Iraq, which covers much of the area long known as Iraqi Kurdistan. One of the few scholars who has done research during the Saddam Hussein regime, King offers a sensitive interpretation of the contradiction resulting from the intersection of tradition with modernity, exploring the ways that residents connect socially through patron-client relationships and as people belonging to gendered categories